Pengaruh Penambahan Strain Counter Strain (Scs) Pada Micro Wave Diathermy (Mwd) Dan Streching Terhadap Penurunan Nyeri Pada Kasus Piriformis Syndrome - Fata, Alif Saiful; , Isnaini Herawati S.Fis.,S.Pd,.M.Sc (2016)
Background : Piriformis syndrome is a reversible compression on the sciatic nerve by the piriformis muscle. This condition can cause severe pain in the region and buttocks, hip and sciatica, with pain radiation towards the thighs, legs, feet and toes. In piriformis syndrome, piriformis muscle tension or spasm of the sciatic nerve can be pressed towards the anterior and inferior. The resulting severe pain conditions can become chronic and cause weakness (Fishman, 2009). Objective : Provide an overview of physiotherapy in the condition of piriformis syndrome using additional strain counter strain (SCS) to reduce pain. Methods : This research uses quasi-experimental research design used in this research is by using pre and post test with control group design. Group I use the additional strain counter strain (SCS) and group II without adding strain counter strain (SCS), for 4 weeks with a frequency of 2x time a week. Because of the number of samples for a bit so complied with the non parametric test. Test the effect of using the Wilcoxon signed ranks test and then test the effect of different uses whithney man test. Results : There was an effect on group I once performed statistical tests using the Wilcoxon signed ranks test was obtained p-value 0.003 and group II results p-value of 0.005, and there are differences in the effect after the test statistic obtained using man whithney test p-value of 0.001. Conclusion : There is a difference between the effect of the addition of strain counter strain (SCS) and without the addition of strain counter strain (SCS) in cases of piriformis syndrome in pain reduction.